Identifying Sensitive Windows of Exposure to NO2 and Fetal Growth Trajectories in a Spanish Birth Cohort. Issue 3 (21st February 2022) - Whitworth, Kristina W.; Rector, Alison; Ish, Jennifer; Chauhan, Suneet P. J.; Ibarluzea, Jesús; Guxens, Mònica; Swartz, Michael D.; Symanski, Elaine; Iñiguez, Carmen
Abstract : Background: We previously identified associations between trimester-specific NO2 exposures and reduced fetal growth in the Spanish INfancia y Medio Ambiente (INMA) project. Here, we use temporally refined exposure estimates to explore the impact of narrow (weekly) windows of exposure on fetal growth. Methods: We included 1, 685 women from INMA with serial ultrasounds at 12, 20, and 34 gestational weeks. We measured biparietal diameter (BPD), femur length, and abdominal circumference (AC) and from them calculated estimated fetal weight (EFW). We calculated z-scores describing trajectories of each parameter during early (0–12 weeks), mid (12–20 weeks), and late (20–34 weeks) pregnancy, based on longitudinal growth curves from mixed-effects models. We estimated weekly NO2 exposures at each woman's residence using land-use regression models. We applied distributed lag nonlinear models to identify sensitive windows of exposure. We present effect estimates as the percentage change in fetal growth per 10 μg/m 3 increase in NO2 exposure, and we calculated cumulative effect estimates by aggregating estimates across adjacent lags. Results: We identified weeks 5–12 as a sensitive window for NO2 exposure on late EFW (cumulative β = −3.0%; 95% CI = −4.1%, −1.9%). We identified weeks 6–19 as a sensitive window for late growth in BPD (cumulative β = −2.0%; 95% CI = −2.7%, −1.4%) and weeks 8–13 for AC (cumulative β = −0.68%; 95% CI = −0.97%, −0.40%). We found suggestive evidence that third trimester NO2 exposure is associated with increased AC, BPD, and EFW growth in late pregnancy. Conclusions: Our findings are consistent with the hypothesis that NO2 exposure is associated with alterations in growth of EFW, BPD, and AC dependent on the specific timing of exposure during gestation.